Maturity Level Risk Assessment in Media Companies Using the ISO 27001 Framework - Wijaya, Anne Ivena; Lestiani, Dwi Indah; Damayanti, Yeni Rosa; Sugiono, Adinda Ayu Putri; Huanggino, Sherissa Callista (Universitas Negeri Surabaya, 2024)
This study aims to assess the maturity level of information security in media companies using the ISO 27001 framework. With the rapid growth of the media industry and increasing cyber security risks, media companies must ensure that their information security systems meet applicable international standards so that existing data can be properly protected. This article uses the PRISMA method, which analyzes sources from articles or papers found on Publish or Perish. The research focuses on article sources that discuss the application of the ISO 27001 framework in companies and the Maturity Level of media companies. The results show that applying the ISO 27001 framework in conducting Maturity Level Assessments in media companies is very important to improve information security and reduce the risk of data leakage. This research also provides an important understanding of the application of the ISO 27001 framework in the media industry and offers guidance for media companies to improve their security maturity level. The limitations of this research are IDN Media as a single case study, so the generalizability of the findings may be limited and the evaluation that only focuses on certain aspects, such as the use of SE, and does not cover all information security domains.